Incarvillea uniflora (Bignoniaceae), a new species from Hengduan Mountains, southwest China - Xia, Changying; Lan, Xiaozhong; Zuo, Youwei; Lin, Le; Deng, Hongping (Phytotaxa, 2021)
The Hengduan Mountains, as one important biodiversity hotspots in the world, is notable for its high habitat heterogeneity and extreme plant diversity which including many endemics species. Incarvillea uniflora, a new species is described from Hengduan Mountains. The new species is similar to I. himalayensis in having red corolla, stemless, solitary flower, capsule 4-angled and winged seeds, but differs by the characters of stable simple leaves, long triangular calyx lobes and solitary or clustered flowers. It is considered to be Data Deficient (DD) due to the lack of further field investigation.